2008
DOI: 10.1002/dc.20976
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of repeat cytology at the time of first colposcopy

Abstract: The value of repeat cytology in the detection of high-grade preinvasive or invasive disease was analyzed at the time of colposcopy in cases of patients with abnormal referral cytology. A series of 136 patients with squamous abnormalities in their referral cytology, who had undergone repeat cytology and for whom outcome had been established, were included in the study. Final diagnosis consisted of 27 negative results (20%), 37 cases of CIN1 (27%), 31 CIN2 (23%), 39 CIN3 (29%), and 2 (1%) cases of squamous cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These results are in agreement with findings from studies that evaluated the performance of cytopathology using histopathology as the gold standard. In these studies, the frequency of results confirmed by histopathology ranged from 62.8 to 86.6% [24,25,31,32,33]. Sensitivity ranged from 51.0 to 91.6% [33,34,35,36,37,38,39,40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with findings from studies that evaluated the performance of cytopathology using histopathology as the gold standard. In these studies, the frequency of results confirmed by histopathology ranged from 62.8 to 86.6% [24,25,31,32,33]. Sensitivity ranged from 51.0 to 91.6% [33,34,35,36,37,38,39,40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Michelow et al [30] reported that 16/19 (84.0%) cases identified at RR-100% were confirmed at repeat cytopathology and, even though our rates of agreement are lower, the result of repeat cytopathology confirmed 44.5% of cases identified at RPS and only 22.2% of cases identified at RR-100%. The studies by Lapin et al [24] and Alves et al [31] reported that 62.4 and 80.9% of cytopathology examinations, respectively, were abnormal on repeat cytopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Women with negative HPV results are referred for a followup cytology after one year. 16,17 Screening for hrHPV could provide 60-70% higher protection from CC than cytology screening. 18 However, HPV DNA or mRNA testing is not yet readily available in the South African public sector setting.…”
Section: Introductionmentioning
confidence: 99%